Menelisik Eksistensi Tuhan, Islam, dan Al-Qur’an Perpsektif Karen Armstrong - Umi Wasilatul Firdausiyah (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2021)
The discourse of this study is in the form of Karen Armstrong's thoughts about the existence of God, the Prophet Muhammad and the Qur'an, which began with her search for God by becoming a nun. In examining Armstrong's thinking, the writer uses a type of research library approach with descriptive-analysis method which is assisted by Hans George Gadamer's hermeneutic theory. The results of this study are in the form of an understanding that in Karen Armastrong's view of God, the Prophet Muhammad, and the Qur’an, in the process of searching for god, a sense of curiosity about Islam grows and gives rise to Armstrong's admiration for the Prophet Muhammad, whose ideas are seen in a early prophetic history while receiving revelations in the cave of Hira. God here is Allah in Islam, and the existence o the Prophet Muhammad as a representation of Islam, and the Qur’an as the holy book of Muslim that gives the mission of God.Armastrong's perspective expressed in his writings has implications for the religion of Islam, in the form of a contribution to the treasures of early understanding of God, Islam, and the Qur’an, to the development of the perspective of contemporary Muslim scholars.